2022
DOI: 10.1126/sciadv.abh2445
|View full text |Cite
|
Sign up to set email alerts
|

The microdissected gene expression landscape of nasopharyngeal cancer reveals vulnerabilities in FGF and noncanonical NF-κB signaling

Abstract: Nasopharyngeal cancer (NPC) is an Epstein-Barr virus (EBV)–positive epithelial malignancy with an extensive inflammatory infiltrate. Traditional RNA-sequencing techniques uncovered only microenvironment signatures, while the gene expression of the tumor epithelial compartment has remained a mystery. Here, we use Smart-3SEQ to prepare transcriptome-wide gene expression profiles from microdissected NPC tumors, dysplasia, and normal controls. We describe changes in biological pathways across the normal to tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…84 Also, reduced expression of Sprouty1 in nasopharyngeal tumours showed that EBV-mediated transformation was associated to FGF signalling. 85…”
Section: Oncogenic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Also, reduced expression of Sprouty1 in nasopharyngeal tumours showed that EBV-mediated transformation was associated to FGF signalling. 85…”
Section: Oncogenic Virusesmentioning
confidence: 99%
“…Nasopharingeal epithelium transformation, associated to EBV infection, was shown to be promoted by viral protein LMP1‐activated FGFR1 84 . Also, reduced expression of Sprouty1 in nasopharyngeal tumours showed that EBV‐mediated transformation was associated to FGF signalling 85 …”
Section: Viral Infection and Fgfsmentioning
confidence: 99%
“…The activity of NF-kB signals has been reported to contribute to metabolic alteration (Mauro et al, 2011;Johnson and Perkins, 2012). In NPC, aberrant activation of NF-kB pathway, which may result from the inactivating mutations of NF-kBnegative regulators such as NFKBIA, CYLD, and TNFAIP3 (Zheng et al, 2016;Li et al, 2017), was universally observed and it is believed to be closely related to the infection of EBV (Lo et al, 2006;de Oliveira et al, 2010;Tay et al, 2022). Consistently, EBV infection was showed to downregulate the expression levels of CYLD in NPC cells (Li et al, 2021), and CYLD deficiency could increase the transcriptional activity of PFKFB3, which is a key regulator of glycolysis, to enhance glycolysis (Wang et al, 2022).…”
Section: Ebv-encoded Latent Membrane Proteinsmentioning
confidence: 99%
“…Aberrantly activated FGF signaling is involved in the accumulation of tumor-infiltrating MDSCs and M2-TAMs [ 23 ], remodeling the metabolism of NPC cells and promoting metastasis. Therefore, FGF2/FGFR2 may be a crucial target in NPC [ 24 ]. FGF/FGFR inhibitors promote further activation and infiltration of effector T cells into the TME by normalizing tumor vasculature.…”
Section: Introductionmentioning
confidence: 99%